GAPDH regulates cellular heme insertion into inducible nitric oxide synthase - Chakravarti, Ritu (National Academy of Sciences, 2010)
Heme proteins play essential roles in biology, but little is known about heme transport inside mammalian cells or how heme is inserted into soluble proteins. We recently found that nitric oxide (NO) blocks cells from inserting heme into several proteins, including cytochrome P450s, hemoglobin, NO synthases, and catalase. This finding led us to explore the basis for NO inhibition and to identify cytosolic proteins that may be involved, using inducible NO synthase (iNOS) as a model target. Surprisingly, we found that GAPDH plays a key role. GAPDH was associated with iNOS in cells. Pure GAPDH bound tightly to heme or to iNOS in an NO-sensitive manner. GAPDH knockdown inhibited heme insertion into iNOS and a GAPDH mutant with defective heme binding acted as a dominant negative inhibitor of iNOS heme insertion. Exposing cells to NO either from a chemical donor or by iNOS induction caused GAPDH to become S-nitrosylated at Cys152. Expressing a GAPDH C152S mutant in cells or providing a drug to selectively block GAPDH S-nitrosylation both made heme insertion into iNOS resistant to the NO inhibition. We propose that GAPDH delivers heme to iNOS through a process that is regulated by its S-nitrosylation. Our findings may uncover a fundamental step in intracellular heme trafficking, and reveal a mechanism whereby NO can govern the process.